The effect of addition of fish oil in commercial feed on growth of carp (Cyprinus carpio) - Khalil, Munawwar; Salamah, Salamah; Azdami, Chairul (Universitas Malikussaleh, 2022)
In carp farming, it is not enough to rely solely on efforts to spur the growth of the fish, but it needs to be accompanied by efficient measures for the feed, this can be done by improving the quality of feed, especially the Feed energy. The source of fat that can be added to feed as an energy source is fish oil and lecithin. This research was aimed to findout the impact of the given various doses addition of the fish oil in the fish woof and to find out the best doses of the fish oil through the growth, the feed conversion ratio and the progression of carp fish life The study was conducted on December to January at Hatchery and Tecnology Aquaculture Laboratory, Faculty of Agriculture, University of Malikussaleh. The method used a nonfactorial completely randomized design with four treatments and three replications, namely A (fish oil 0,90 %), B (fish oil 1,2 %), C (fish oil 1,5 %) and D commercial feed (control). The result showed that fish oil with different doses had very significant different effect on growth, significantly different to feed conversion ratio and not significantly different to survival. the best treatment was found in treatment C by giving fish oil 1,5 %.Keywords: feed; fish oil; growth; carp